Oral care practices of adults in Turkey - Koseoglu, Merve; Bal, Ozge; Turkan, Hatice Bilge; Cetin, Beyza; Tascioglu, Muhammed Nuri; Aydin, Nurullah; Sancar, Ozgur; Altindis, Selma (Makara Journal of Health Research, 2020)
Background: Information on oral health practices can play a key role in improving a community’s oral health status. The aim of this study was to determine oral healthcare practices of Turkish individuals. Methods: A questionnaire was randomly given to 351 individuals, all of them older than 18 years. This cross-sectional study data were analyzed using descriptive statistical methods and chi-square test. Statistical significance was evaluated at p < 0.05. Results: According this study, 62.1% of individuals visited the dentist only when they needed to. Furthermore, 58% of individuals brushed their teeth twice a day; 12.5% of them used miswak; 50.4% used dental floss, toothpicks, or mouthwash; and 86.6% stated that they didn’t use any other herbal/traditional tooth cleaning method. Additionally, 39.8% of the individuals reported that they ate sweetened foods 1–2 times a day, and 33.6% of them drank acidic beverages 1–2 times a month. Although the frequency of visiting a dentist and using herbal/traditional practices did not differ among individuals (p ˃ 0.05), frequency of consuming sweetened food did differ (p = 0.032). Conclusions: Toothbrushing and interdental cleaning habits differed among individuals, while frequency of dentist visits and alternative methods of cleaning teeth did not differ.